Peran mahasiswa dalam menjaga moderasi beragama di era digital - Zen, Mazza Luna Fon (Maliki Interdisciplinary Journal, 2025)
Religious moderation is an essential effort to preserve harmony in Indonesia’s highly diverse society. Promoted by the Ministry of Religious Affairs, religious moderation emphasizes the principles of tawassuth (moderation), tawazun (balance), i’tidal (justice), and tasamuh (tolerance) as the foundation of religious life. In the digital era, university students play a strategic role in strengthening these values, as they serve not only as academic agents but also as social agents who actively engage in the digital public sphere. This study aims to examine the role of students in maintaining religious moderation amidst the challenges of globalization and the rapid development of digital technology. The research applies a literature study method by analyzing scientific articles, community service reports, and academic references related to religious moderation. The findings highlight three main roles of students: as digital literacy agents capable of filtering information and producing positive content, as peace-builders who promote interfaith dialogue in plural societies, and as promoters of national unity who internalize values of tolerance and inclusivity in the face of transnational ideologies. Moreover, the use of social media and cyberspace has proven to be effective in embedding religious moderation values among young generations, provided that sufficient literacy accompanies it. Therefore, students are not merely consumers of information but also producers of ideas who can create a healthy, tolerant, and civilized digital public sphere, while simultaneously strengthening Indonesia’s national identity.